2017
DOI: 10.1002/ps.4756
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions between a variety of insecticides and an ergosterol biosynthesis inhibitor fungicide in dietary exposures of bumble bees (Bombus terrestris L.)

Abstract: Our findings suggest that P450-based detoxification processes are differentially important in mitigating the toxicity of certain insecticides, even those of the same chemical class. Our evidence that cocktail effects can arise in bumble bees should extend concern about the potential impacts of agrochemical mixtures to include wild bee species in farmland. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 38 publications
4
54
0
1
Order By: Relevance
“…Besides neonicotinoids, flower‐visiting insects are routinely exposed to other insecticides, fungicides and herbicides, of which single and combined effects in field conditions are largely unknown (Botías, David, Hill, & Goulson, ; Tosi, Costa, Vesco, Quaglia, & Guido, ). Though not toxic to pollinators, fungicides may weaken their resistance to pathogens (Pettis et al., ) and cause synergistic mortality with insecticides (Raimets et al., ). Herbicides harm pollinators indirectly by reducing diversity of their food resources (Goulson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides neonicotinoids, flower‐visiting insects are routinely exposed to other insecticides, fungicides and herbicides, of which single and combined effects in field conditions are largely unknown (Botías, David, Hill, & Goulson, ; Tosi, Costa, Vesco, Quaglia, & Guido, ). Though not toxic to pollinators, fungicides may weaken their resistance to pathogens (Pettis et al., ) and cause synergistic mortality with insecticides (Raimets et al., ). Herbicides harm pollinators indirectly by reducing diversity of their food resources (Goulson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Lundin et al after analyzing 268 publications involving neonicotinoid researches, found that thiamethoxam was the second most studied component with 34%, in 73 studies. Recently, articles evaluating the exhibition of the thiamethoxam on pollinators have been pointed out as sublethal effects on behavior, locomotion, and memory, metabolism and immunity, reproduction, and synergistic effects of additional pesticides with neonicotinoids …”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (39) fed honeybees with a commercial formulation of imidacloprid in sucrose solution and noted higher cytochrome P450 activity. According to another study (40), honeybees mainly rely on cytochrome P450 monooxygenases to counter the toxic effects of this imidacloprid formulation, but other authors claim that every active substance is countered by different enzymes, at least in bumblebees (41).…”
Section: Honeybeesmentioning
confidence: 99%